2000
DOI: 10.1076/1385-4046(200005)14:2;1-z;ft149
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Normative Data for the Mattis Dementia Rating Scale for Use with Urban, Elderly Medical Patients

Abstract: Normative data for the Mattis Dementia Rating Scale (MDRS), stratified by age and education, are provided for use with older adults (ages 61-94) in urban medical settings. Age and education accounted for the greatest amount of variance in MDRS performance. Gender and race were also associated with total MDRS scores, though to a lesser extent. The present normative data are more appropriate for use with older patients seen in urban medical settings than normative data obtained from samples of better-educated, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
2
24
0
4
Order By: Relevance
“…The results found in this study confirm the influence of the variables age and schooling in the DRS 12,20,24,25 . The Conceptualization subscale, which contains tasks related to abstraction and semantic memory, showed sensitivity both to the variables age and schooling.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results found in this study confirm the influence of the variables age and schooling in the DRS 12,20,24,25 . The Conceptualization subscale, which contains tasks related to abstraction and semantic memory, showed sensitivity both to the variables age and schooling.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, the data derived from these studies are not considered representative, which has led researchers to validate the scale in specific populations 12,22,23 . Recent studies have shown the influence of age and schooling on performance in the DRS, suggesting that a single cutoff score is not appropriate for all groups of elderly people 20,[23][24][25] .…”
mentioning
confidence: 99%
“…A metodologia empregada deveria tentar isolar a variável escolaridade da variável idade e de gênero, que interferem nas avaliações neuropsicológicas. Na análise dessas variáveis, mesmo estando ciente da influência do envelhecimento sobre a MDRS 11,[14][15][16] , verificou-se que a idade não representou correlação significativa em relação aos resultados da escala, o que pode ser devido à estreita faixa etária estudada, 64 aos 77 anos, que, talvez, não tenha apresentado uma variação suficiente para mostrar associação com o desempenho da escala.…”
Section: Discussionunclassified
“…Entretanto, deve-se considerar que, na população brasileira, há número maior de mulheres analfabetas que o de homens; portanto, a diferença encontrada, também, pode r e l a c i o n a r-se com variáveis sociais e culturais. Ainda quanto ao gênero, na MDRS, os resultados ainda não alcançaram um consenso sobre sua influência no desempenho dessa escala 15,16,19 .…”
Section: Discussionunclassified
See 1 more Smart Citation